Housing and asthma disparities - Bryant-Stephens, Tyra C.; Strane, Douglas; Robinson, Elizabeth K.; Bhambhani, Sanya; Kenyon, Chén C. (Journal of allergy and clinical immunology, 2021)
The burden of asthma disproportionately affects minority and low-income communities, resulting in racial and socioeconomic disparities in asthma prevalence, asthma exacerbations, and asthma-related death. Social determinants of health are increasingly implicated as root causes of disparities, and healthy housing is perhaps the most critical social determinant in asthma health disparities. In many minority communities, poor housing conditions and value are a legacy of historical policies and practices imbued with structural racism, including redlining, displacement, and exclusionary zoning. As a result, poor-quality, substandard housing is a characteristic feature of many underrepresented minority communities. Consequently, structurally deficient housing stock cultivates home environments rife with indoor asthma triggers. In this review we consider the historical context of urban housing policies and practices and how these policies and practices have contributed to the substandard housing conditions for many minoritized children in the present day. We describe the impact of poor housing quality on asthma and interventions that have attempted to mitigate its influence on asthma symptoms and health care utilization. We discuss the need to promote asthma health equity by reinvesting in these neighborhoods and communities to provide healthy housing.